Vigilant Attention - GARAVAN, HUGH PATRICK (MIT Press, 2004)
When train drivers pass through warning or stop signals ? as they do many thousands of times per day throughout the world ? this is an example, we argue, of an inefficiency in the functioning of a right hemispheric, fronto-parietal attention system for `vigilant attention?. Closely linked to Posner?s notion of the `alerting? system, vigilant attention is distinct from Posner?s other two functionally and anatomically distinct supramodal attentional systems ? selection and control respectively. We review evidence for the validity of this 3-factor typology of attention, and clarify the frequently articulated misconception that `vigilance? and `sustained attention? are defined by time-on-task decrements over extended periods of test performance, as originally proposed by Mackworth. Rather, we show that vigilant attention involves a half-life measured in seconds rather than minutes, and is most sensitively measured in situations where routine action cycles are under way. We further show evidence of how everyday action error propensities link to specific functional brain activation patterns and how Attention Deficit Disorder can be an excellent model system for malfunctioning of this system. We end by demonstrating the possibilities for rehabilitation of this system.
PUBLISHED
Keywords: Psychology